Transformational leadership and organizational citizenship behavior: Moderating organizational trust - Wahid Sumarjo; Dedeh Kurniasih; Wahyudi Wahyudi (Jurnal Mantik, 2024)
Human factors are critical in society's social, economic, and political development, as well as the effectiveness and efficiency of organizations. In addition, for organizations to succeed in changing conditions, they need employees who are willing to contribute to the effectiveness and development of the organization beyond what is expected without being limited to formal job descriptions. Organizational citizenship behavior is needed to achieve this. This study examines how transformational leadership can affect organizational citizenship behavior moderated by organizational trust. The method used in this research is the PLS-SEM approach, with a total sample of 165 respondents. This study found that transformational leadership can positively and significantly affect organizational citizenship behavior, but organizational trust cannot have a significant effect